The Effectiveness of Reality Group Counseling Confrontation and Storytelling Techniques to Increase Self-Acceptance - Bangkit, Jean Rala; Mulawarman, Mulawarman; Awalya, Awalya (Universitas Negeri Semarang, 2022)
Low self-acceptance can cause students to be less optimum in developing their potential and adaptation. This research aimed at examining the effectiveness of reality group counseling with confrontation and storytelling techniques to increase the self-acceptance of students at SMK Negeri 11 Semarang. It used a pretest-posttest control group design and involved 24 tenth grade students selected using a purposive sampling technique. Those students were grouped into 3 and given a confrontation technique for 5 sessions, storytelling for 5 sessions, and no treatment for the control group. Findings indicated that both confrontation and storytelling techniques were effective to increase self-acceptance. In detail, the group counseling with a confrontation technique gave better results. Finally, implications and suggestions are provided to support the implementation of reality group counseling.